Along the border: affective promotion or inhibition of conduct in urban spaces / A lo largo de la frontera: promoción o inhibición afectiva de la conducta en los espacios urbanos. Issue 1 (2nd January 2019) - Tateo, Luca; Marsico, Giuseppina
Abstract: The concepts of borders, tensegrity and goal-oriented meaningful conduct are used to study the conditions in which affects and conducts can (or cannot) emerge in urban spaces. We assume psychological phenomena are liminal and emerge in the border zones between different individual and collective states. The main focus of the study is the process of affective meaning-making that takes place at specific locations (the border zones) in urban living. Through an example of autoethnography, we try to understand how the symbolic space is used in everyday life to produce, maintain and demolish signs that self-regulate and hetero-regulate complex atmospheres, affects and conducts.